Consecutive-type Reliability Structures Under Warm Standby Redundancy: Some Advances - Triantafyllou, Ioannis S. (Journal of Graphic Era University, 2024)
In the present article, we investigate two different reliability structures, which belong to the class of consecutive-type systems under redundancy policy. The resulting structures consist of n independent components, but they also dispose warm standby ones. The distribution of the number of working warm components at the time of system’s failure is studied in some detail. Among others, explicit expressions for determining the corresponding probability mass function are established. A short discussion for future work is also developed.